Article Commentary: The Cold Dusty Harmattan: A Season of Anguish for Cardiologists and Patients - Basil N. Okeahialam (SAGE Publishing, 2016)
Human health and disease often demonstrate seasonal patterns. Knowledge of these aspects aids anticipation and planning. Numerous studies have shown that hypertension and cardiovascular diseases demonstrate a seasonal pattern. The Harmattan, the cold dusty season in Sub-Saharan Africa, is the season of greatest concern in this regard. In this commentary, the author draws on his and other researchers' studies to explain the grounds for onset and worsening of existing cardiovascular diseases. As implied in the title, it is a season that puts great strain on the cardiologist and the health system, as well as greater disease burden on the patient. This should be taken into consideration in planning and pooling of resources for effective patient management and mitigation of impact of disease.